Implication of Human UGT2B7, 2B15, and 2B17 in 19-Norandrosterone Metabolism - Strahm, Emmanuel; Sjöberg, Ulf; Garle, Mats; Rane, Anders; Ekström, Lena (Frontiers in Endocrinology, 2013)
Nandrolone (19-nortestosterone) is an anabolic androgenic steroid commonly abused for doping purposes. Nandrolone is mainly metabolized in the liver into 19-norandrosterone prior to glucuronidation and excretion through urine over an extended period of time. Several UGTs (i.e. UGT2B7, UGT2B15 and UGT2B17) are thought to be the major enzymes responsible for conjugation of androgens in human. An in-vitro study using recombinant enzymes expressed in insect cells showed that UGT1A4 and UGT2B7 are the two main enzymes responsible of 19-norandrosterone glucuronidation. However, the identity of the enzyme involved in nandrolone metabolism in vivo together with their relative contribution and regulation remain unknown. Inhibition assays using human liver microsomes incubated with 19-norandrosterone and selective inhibitors confirmed that UGT2B7 and UGT2B15 are involved in 19-norandrosterone glucuronidation, since the presence of the specific UGT2B7 and UGT2B15 inhibitors gemfibrosil and valproic acid inhibited the 19-norandrosterone glucuronidation by 35 and 45 %, respectively. Human liver microsomes were genotyped for UGT2B15 D85Y, UGT2B7 H268Y and the UGT2B17 deletion polymorphism. The glucuronidation activity on 19 norandrosterone was significantly higher in UGT2B15 DD than in the other UGT2B15 genotypes (p<0.05). Moreover, human liver cancer HepG2 cells were exposed to androgens to determine if the transcriptional activity of the genes of interest was affected. Only UGT2B7 mRNA expression was significantly increased (1.8-folds) after incubation with nandrolone decanoate. These results show that the UGT2B7 and UGT2B15 are involved in 19-norandrosterone glucuronidation and that the UGT2B15 polymorphism (D85Y) is the only UGT genetic variation that influences the glucuronidation activity. This could partly explain the inter-individual variation in 19 norandrosterone excretion.